Identificação da Utilização de Recursos Naturais por uma Comunidade do entorno da UHE Curuá-Uma - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2003)
The human populations of the Amazon, located in the countryside, maintain a continuous exchange relationship with the various natural resources, on which both their production and their social reproduction directly depend. The present work aims at identifying the use of natural resources by the Xavier community, located on the banks of the Curuá-Una HPP lake, in Santarém/Pará. The methodology used included semi-structured interviews, as well as participant observation through the monitoring of the community members' daily activities. According to a sample of 50% of the families, a total of 144 people resided in the Xavier community. Among the activities related to the use of natural resources, fishing, hunting, and gathering fruits from the forest; the extraction of babassu straw for building houses, and the collection of medicinal products can be highlighted. Agriculture was considered by 73% of the interviewed families as the main activity developed. They plant rice, beans, corn, and especially manioc, which is used to produce flour, the basis of the community's diet and one of the main sources of income. The population of Xavier can be compared to the socio-environmental category of "migrants/ frontiersmen" created by Lima and Pozzobon (2001), in which small rural workers establish themselves as squatters on the agricultural expansion fronts, using deforestation as an artifice to legitimize their right to occupation. Although most of the population is in the area since a period after the implementation of the HPP, the formation of the lake was one of the determining factors for the establishment of populations in the area, due to the increased navigability of the Curuá-Una River and the consequent relationship of use with the natural resources of the region.
Identification of the Use of Natural Resources by a Community Surrounding the Curuá-Uma Hydroelectric Plant
Keywords: Agricultores; Recursos Naturais; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA